Addiction to Gadget Use with Sleep Quality and Adolescent Achievement Index in Adolescents - Faisal Faisal; Asnawi Abdullah; Fahmi Ichwansyah; Radhiah Zakaria; Maidar Maidar (Indonesian Journal of Global Health Research, 2024)
Generation Z today cannot go a day without gadgets. Over time, Generation Alpha is likely to become similarly preoccupied with gadgets, as they have been influenced by technology since birth and view it as an essential tool for both school and other activities. Excessive gadget use negatively impacts the quantity and quality of sleep. This study employed a cross-sectional design to analyze the relationship between gadget addiction, sleep quality, and academic performance among adolescents in the coastal and mountainous areas of Pidie Regency. The sample consisted of 337 students from Kembang Tanjong High School and 159 students from Tangse High School, selected using a total sampling technique. Data were analyzed using the Mann-Whitney test and linear regression. The results showed no significant differences in the average sleep quality and gadget addiction levels between adolescents in coastal and mountainous regions. However, there was a significant difference in the average academic performance between these two groups. Factors associated with sleep quality included age, male gender, mothers’ lower education level, gadget addiction, and anxiety. Meanwhile, factors influencing academic performance were male gender, gadget addiction, social media motives, ease of gadget access, depression, and anxiety. Adolescents are encouraged to reduce gadget usage, as it adversely affects sleep quality and academic performance. They can replace gadget usage with positive activities such as physical exercise, playing sports, socializing with peers, studying together, and other productive activities.